2016
DOI: 10.1007/s11192-016-2193-x
|View full text |Cite|
|
Sign up to set email alerts
|

How long do top scientists maintain their stardom? An analysis by region, gender and discipline: evidence from Italy

Abstract: This paper examines country-specific factors that affect the three most influential world university rankings (the Academic Ranking of World Universities, the QS World University Ranking, and the Times Higher Education World University Ranking). We run a cross sectional regression that covers 42-71 countries (depending on the ranking and data availability). We show that the position of universities from a country in the ranking is determined by the following country-specific variables: economic potential of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
1
10
0
5
Order By: Relevance
“…However, this evidence is related to ASN, and not to actual promotions. Therefore, this paper may shed some light about the lamented long-standing problem of promotion awarded irrespectively of degree of productivity, promoting also research inactive scholars (Abramo, D'Angelo, & Soldatenkova, 2017). This problem of nepotism and lack of actual meritocracy is also at the base of an apparent missing bias against women in Italian universities: often, the foremost victims of unfair promotions are scholars who are more productive, which in turn are more frequently males (Abramo, D'Angelo, & Rosati, 2016).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, this evidence is related to ASN, and not to actual promotions. Therefore, this paper may shed some light about the lamented long-standing problem of promotion awarded irrespectively of degree of productivity, promoting also research inactive scholars (Abramo, D'Angelo, & Soldatenkova, 2017). This problem of nepotism and lack of actual meritocracy is also at the base of an apparent missing bias against women in Italian universities: often, the foremost victims of unfair promotions are scholars who are more productive, which in turn are more frequently males (Abramo, D'Angelo, & Rosati, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…In some disciplines (such as physical and chemical sciences), women full professors tend to outperform men. However, women are less likely than men to maintain the status of top performers (Abramo et al, 2017). Overall, literature shows that gender plays a role in the promotion process: even if women tend to be less productive, the evidence provided by Bagues and colleagues (2017) shows that women might be discriminated independently of their productivity.…”
Section: Gender Dynamics In the Italian Asn Systemmentioning
confidence: 99%
“…The last VQR assessment of the research output of the CNR from 2011 to 2014 showed that the institution under study here was 1 st amid Italy's public research bodies evaluated in earth sciences, 7 th in physics, 2 nd in medical sciences, 4 th in life sciences, and 3 rd in chemical sciences [ 39 ]. Several scientometric studies have investigated Italy's university system [ 38 , 40 , 41 ] and reorganization of the CNR, which clearly showed a shift from basic to applied research and consultancy to firms offered by new institutes that are more and more operating as quasi-business firms [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, with the instrument used, this could not be explored. And third, only a cross-sectional study could be performed; thus, no changes over time could be analyzed (for instance, the identification of the persistence of top performance over time as in Kelchtermans and Veugelers ( 2013 ), or the length of periods of the stardom of stars as in Abramo et al ( 2017b ) could not be explored).…”
Section: Discussionmentioning
confidence: 99%